2020
DOI: 10.1109/jtehm.2020.2987008
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Simulator for the Strategic Positioning of Aerial Ambulance Drones Reaching Out-of-Hospital Cardiac Arrests: A Genetic Algorithmic Approach

Abstract: Objective: The Internet of Things provide solutions for many societal challenges including the use of unmanned aerial vehicles to assist in emergency situations that are out of immediate reach for traditional emergency services. Out of hospital cardiac arrest (OHCA) can result in death with less than 50% of victims receiving the necessary emergency care on time. The aim of this study is to link real world heterogenous datasets to build a system to determine the difference in emergency response times when havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Studies also continue to explore the retrieval and use of an AED delivered via drone and report positive experiences from participants interacting with a drone during OHCA in a community setting [ 28 , 29 ]. Mackle et al (2020) [ 30 ] recently linked real world datasets in Northern Ireland and built a system to determine the difference in emergency response times when having aerial ambulance drones available compared to response times when depending solely on traditional ambulance services and lay rescuers who would use nearby publicly accessible defibrillators to treat OHCA victims. Mackle et al (2020) [ 30 ] found that after the drone network was implemented, publicly accessible AEDs made up 19.74% of responses, ambulances made up 25.66% and drones made up 54.6% of total responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also continue to explore the retrieval and use of an AED delivered via drone and report positive experiences from participants interacting with a drone during OHCA in a community setting [ 28 , 29 ]. Mackle et al (2020) [ 30 ] recently linked real world datasets in Northern Ireland and built a system to determine the difference in emergency response times when having aerial ambulance drones available compared to response times when depending solely on traditional ambulance services and lay rescuers who would use nearby publicly accessible defibrillators to treat OHCA victims. Mackle et al (2020) [ 30 ] found that after the drone network was implemented, publicly accessible AEDs made up 19.74% of responses, ambulances made up 25.66% and drones made up 54.6% of total responses.…”
Section: Discussionmentioning
confidence: 99%
“…Mackle et al (2020) [ 30 ] recently linked real world datasets in Northern Ireland and built a system to determine the difference in emergency response times when having aerial ambulance drones available compared to response times when depending solely on traditional ambulance services and lay rescuers who would use nearby publicly accessible defibrillators to treat OHCA victims. Mackle et al (2020) [ 30 ] found that after the drone network was implemented, publicly accessible AEDs made up 19.74% of responses, ambulances made up 25.66% and drones made up 54.6% of total responses. Such studies along with ours are thus continuing to build the knowledge base for application and adoption of drones in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies [ 20 , 21 , 22 , 23 ] were conducted in Canada, one [ 24 ] in France, two [ 25 , 26 ] in Germany, five [ 27 , 28 , 29 , 30 , 31 ] in Sweden, two [ 32 , 33 ] in the United Kingdom, one [ 34 ] in Ireland, one [ 35 ] in South Korea and 10 [ 18 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] in the United States. These locations varied in geographic scale from counties and towns to entire cities and covered a broad range of urban and rural settings.…”
Section: Resultsmentioning
confidence: 99%
“…38 Mackle et al likewise describe a country-wide algorithmic approach to design an aerial AED-drone network, coordinated among historical OHCA locations, fixed public AEDs retrievable by lay rescuers, and ground EMS stations with ambulance response. 39 The program compared fixed AED versus ground EMS versus simulated drone site determine where to station drones across Northern Ireland. A final model of 78 drone bases was chosen to ensure a nationwide standard (~100%) of AED arrival to a victim in under eight minutes, but also found almost 50% of OHCAs having an AED arrival in under three minutes.…”
Section: Delivery Of Automated External Defibrillators (Aeds)mentioning
confidence: 99%